Efektivitas Penerapan Metode Qişşatu Al-Qur`Ānī untuk Meningkatkan Akhlak Mulia Siswa Kelas IV SD Cirebon Islamic School (CIS) Full Day - Abdullah, Muhammad Luthfi (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to determine whether the method Qur'an story has a significant influence on the development of a noble character. Taken population Elementary School fourth grade students of the CIS, with a cluster sampling technique that is in class IV Roudhoh and class IV Multazam. The design was experimental design really. There are two classes, namely the control class and experimental class. Grade control using conventional methods, while the experimental group was treated using the method Qur`an story. Do pretest and posttest for both classes to assess the noble character of students. The hypothesis is that the Quran story method significantly influences the development of the noble character of students. Tests conducted by the independent samples t-test to compute t and t see table at the significance level of 0.05 with NU = 26. The result t is greater than t table (2.18> 1.71). This indicates that the hypothesis is accepted. Thus, the method Qur`an story significant influence on the development of a noble character of students.